Peak to average power ratio reduction in the orthogonal frequency division multiplexing system using partial transmit sequence - Farhood, Hussein Mohammed (2019)
Orthogonal frequency division multiplexing (OFDM) has been becoming more popular modulation technique in the high-speed wireless communication system. It is used especially in Long Term Evaluation technique (LTE) which depended from the fourth-generation (4G) of wireless communication system. OFDM proves high efficiency to transmit data rate as high as 100 Mbps, the capability to combat multipath fading channel and utilization the whole bandwidth. Although, OFDM technology has more advantages, the same time has some obstacles also. The highest Peak to average power ratio (PAPR) considers the main restrict which cause non-linearity at receiving end. Coding, clipping and phase rotation among many PAPR reduction techniques are proposed to overcome this problem. In this project, we investigated the PAPR reduction performance with PAPR reduction technique partial transmit sequence (PTS). This PAPR reduction method consider sub-part of signal scrambling technique that depend on phase rotation technique in its operation. The simulation results show PTS method have improved the PAPR reduction performance with different parameters. Moreover, different kinds of PTS scheme are also plotted. Generally, PTS technique are leading the PAPR reduction better performance. The results are verified using MATLAB software.